Rhodium(II)-Catalyzed Enantioselective Intermolecular Aziridination of Alkenes - Boquet, Vincent (2022)
C4-Symmetrical dirhodium(II) tetracarboxylates are highly efficient catalysts for the asymmetric intermolecular aziridination of substituted alkenes with sulfamates. The reaction proceeds with high levels of efficiency and chemoselectivity to afford aziridines with excellent yields of up to 95% and enantiomeric excesses of up to 99%. The scope of the alkene aziridination includes mono-, di-, and trisubstituted olefins as well as the late-stage functionalization of complex substrates. The reaction can be performed on a gram-scale with a catalyst loading of 0.1 mol %. Our DFT study led us to propose a two-spin-state mechanism, involving a triplet Rh-nitrene species as key intermediate to drive the stereocontrolled approach and activation of the substrate.